Jarros, adornos ou profissionais? um olhar sobre o papel da mulher na Polícia Militar da Paraíba - Silva, Sandra Silvestre do Nascimento (2020)
In this thesis, the objective was to study how the military police's cultural institutionality, associated with an androcentric context, constitutes barriers for the acceptance of women in the Military Police of Paraíba. To this end, based on a qualitative approach, through auto-ethnographic research and interviews with 30 police officers, a reflection on the insertion of the first soldiers included in the Corporation was initially carried out to understand the process of incorporating the habitus into the police. Following the research, the results of the interviews, conversations on WhatsApp and the author's participation as a native in several institutional events were presented, which served as important material for the analysis of the professional performance of police women from Paraíba. In the results, we found that the pioneer soldiers went through difficulties to incorporate the habitus, mainly due to the rigidity of the militarism, hierarchy and discipline triad in demanding that the military respond to the dominant cultural arbitrary. It was also found that the police undergo resistance to work in the Corporation because they are considered inadequate for the profession, which, according to the dominant discourse, is linked to characteristics such as strength and virility, attributes that are socially related to men, configuring themselves in violence of gender inside the barracks.